A comparison of local-global visuospatial processing in autism spectrum disorder, nonverbal learning disability, ADHD and typical development. (August 2020) - Cardillo, Ramona; Vio, Claudio; Mammarella, Irene C.
Highlights: Examines local-global visuospatial processing in children with ASD, NLD and ADHD. Different profiles of visuospatial abilities emerge for each clinical group. The local-global processing index discriminates among groups in visuo-constructive task. Results might help to further understand cross-disorder similarities and differences. Abstract: Background: Research on visuospatial functioning has revealed cognitive challenges for children with autism spectrum disorder (ASD), nonverbal learning disability (NLD) and attention deficit hyperactivity disorder (ADHD). These disorders are characterized by some overlapping symptoms, making their diagnosis a challenge. Aims: The study aims to clarify the role of visuospatial abilities in their neuropsychological profiles by investigating different visuospatial domains and their interplay with the local-global processing. Method and procedures: Participants (N = 150) with ASD, NLD, or ADHD were compared with typically-developing (TD) children on visuospatial processing speed, visuo-perceptual abilities, visuo-constructive abilities, and visuospatial working memory. Generalized mixed-effects models were performed and receiver operating characteristic curves were estimated to express the usefulness of a local-global processing index in discriminating groups. Outcomes and results: The NLD group was impaired in all domains; children with ADHD revealed a heterogeneous profile, with greater impairments in visuospatial processing speed; ASD and TD groups were comparable. The local-global processing index had predictive power in discriminating among groups in visuo-constructive task. Conclusions and implications: The study of visuospatial abilities of children with ASD, NLD and ADHD might help to understand strengths and weaknesses in their neuropsychological profile and to differentiate between them. Clinical implications of these findings are discussed.